The Evaluation of The Relation Between Nasal Polyp Etiopathogenesis and the Amount of Biofilm - Kazım Bozdemir; Yuce İslamoglu; Nurcan Özyurt Koçakoğlu; Serkan Şerifler; Selami Candan; Bülent Ulusoy; Elif Ersoy Çallıoğlu (Genel Tıp Dergisi)
Objective: To evaluate the effect of biofilm layer on polyp formation in nasal polyposis by comparing the amount of biofilm layer on polyp tissue and the normal mucosa. Material and Methods: This study is a prospective study. 14 patients who underwent functional endoscopic sinus surgery (FESS) for nasal polyposis were evaluated. Patients were had no history of previous FESS. Tissue samples were obtained from lower turbinate (Group 1 n:14) and from nasal polyp (Group 2, n:14) of the same nasal cavity. Biofilm presence was identified using scanning electron microscopic (SEM) morphological findings. In biofilm positive samples, the presence of biofilm in less than 25% of the surface area was classified as (+), between 25-50% as (++) , and over 50% as (+++). Results: In Group 2, with SEM imaging, (+++) biofilm presence was detected in 9 patients and (++) biofilm was detected in 5 patients. In Group 1, no biofilm was detected 8 patients, while; (+++), (++), and (+) biofilm presence was detected in 1, 2, and 3 patients respectively. Significant difference was found between group 1 and group 2 with respect to the amount of biofilm according to SEM (p =0.000). Conclusion: In samples, statistically significant difference was found between polyp tissue and normal mucosa in terms of the amount of biofilm. However, further studies with larger patient series are required in order to reach a definitive conclusion on the effect of biofilm on pathogenesis of polyp.